Intratumoral Heterogeneity of MAGE-C1/CT7 and MAGE-C2/CT10 Expression in Mucosal Melanoma. (16th June 2015) - Curioni-Fontecedro, A.; Pitocco, R.; Schoenewolf, N. L.; Holzmann, D.; Soldini, D.; Dummer, R.; Calvieri, S.; Moch, H.; Mihic-Probst, D.; Fitsche, A.
Abstract : Mucosal melanoma is a rare disease, which differs from its cutaneous counterpart genetically and for its clinical behaviour. Moreover this is a heterogeneous disease based on the tissue of origin. As CT7 and CT10 are highly expressed in cutaneous melanoma and are immunogenic in this disease, we analysed their expression throughout the different subtypes of mucosal melanoma and tumor development. We detected a frequent expression of CT7 in primaries and corresponding metastases (55%) as well as for CT10 (30%). This expression resulted to be heterogeneous in the same tumor specimen and moreover influenced by the tissue of origin. Our results support the role of these antigens in immunotherapy for mucosal melanoma.